Analysis of mouse polyomavirus mutants with lesions in the minor capsid proteins - Mannová, Petra; Liebl, David; Krauzewicz, Nina; Fejtová, Anna; Štokrová, Jitka; Palková, Zdena; Griffin, Beverly E; Forstová, Jitka (The Journal of general virology, 2002)
Polyomavirus mutants E, Q and H, expressing non-myristylated VP2, were generated by replacing the N-terminal glycine residue with glutamic acid, glutamine or histidine, respectively. Viruses mutated in either VP2 or VP3 translation initiation codons were also prepared. All mutated genomes, when transfected into murine host cells, gave rise to viral particles. Infectivity of VP2- and VP3- viruses, as measured by the number of cells expressing viral antigens, was dramatically diminished, indicative of defects in the early stages of infection. In contrast, the absence of a myristyl moiety on VP2 did not substantially affect the early steps of virus infection. No differences in numbers of cells expressing early or late viral antigens were observed between wild-type (wt) and E or Q myr- viruses during the course of a life cycle. Furthermore, no delay in virus DNA replication was detected. However, when cells were left for longer in culture, the number of infected cells, measured by typical virus bursts, was much lower when mutant rather than wt genomes were used. In situ, cell fractionation studies revealed differences in the interaction of viral particles with host cell structures. The infectivity of mutants was affected not only by loss of the myristyl group on VP2, but also, and to a greater extent, by alterations of the N-terminal amino acid composition.
Keywords: Cell Line; transfekce; DNA Replication; kapsida; replikace DNA; virové plášťové proteiny; DNA virů; mutace; Mice; kyselina myristová; Capsid Proteins; replikace viru; Capsid; Antigens, Viral; Polyomavirus; kodon iniciační; Codon, Initiator; Mutation; zvířata; Myristic Acid; DNA, Viral; Fibroblasts; Transfection; myši; antigeny virové; buněčné linie; Virus Replication; fibroblasty; Animals